2010
DOI: 10.1103/physrevb.81.014510
|View full text |Cite
|
Sign up to set email alerts
|

Gutzwiller magnetic phase diagram of the undopedttUHubbard model

Abstract: We calculate the magnetic phase diagram of the half-filled t − t − U Hubbard model as a function of t and U , within the Gutzwiller approximation RPA (GA+RPA). As U increases, the system first crosses over to one of a wide variety of incommensurate phases, whose origin is clarified in terms of double nesting. We evaluate the stability regime of the incommensurate phases by allowing for symmetry-breaking with regard to the formation of spin spirals, and find a crossover to commensurate phases as U increases and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
(7 reference statements)
2
19
0
Order By: Relevance
“…In particular, the T = 0 magnetic phase diagram of the cuprates was derived using the time-dependent GA (TDGA) [22]. In the electron-doped cuprates, the magnetic phase diagram is dominated at all dopings by a commensurate π π ( , )antiferromagnetic (AFM) order [22]. In contrast, for the hole doped cuprates, we find a wide doping range over which the magnetic order is incommensurate.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…In particular, the T = 0 magnetic phase diagram of the cuprates was derived using the time-dependent GA (TDGA) [22]. In the electron-doped cuprates, the magnetic phase diagram is dominated at all dopings by a commensurate π π ( , )antiferromagnetic (AFM) order [22]. In contrast, for the hole doped cuprates, we find a wide doping range over which the magnetic order is incommensurate.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, at large doping cuprates behave as Fermi liquids, so that one can hope to obtain information on ordered phases by studying the instabilities that disrupt the Fermi liquid behavior, provided the correlated physics is included in the analysis. We have shown that in the weak and intermediate coupling range, peaks in the bare susceptibility of 2D materials, which determine magnetic instabilities, form a map of the FS, and the dominant instabilities are generally related to the double nesting features [15,22], where two branches of the map cross. In particular, the T = 0 magnetic phase diagram of the cuprates was derived using the time-dependent GA (TDGA) [22].…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations